Experimental observation of conductive edge states in weak topological insulator candidate HfTe5 - Liu, S.; Wang, M. X.; Chen, C.; Xu, X.; Jiang, J.; Yang, L. X.; Yang, H. F.; Lv, Y. Y.; Zhou, J.; Chen, Y. B.; Yao, S. H.; Lu, M. H.; et al. (APL Materials, 2018)
The quantum spin Hall (QSH) effect is widely studied as a novel quantum state in condensed matter physics over the past decade. Recently, it is predicted that the transition metal pentatelluride XTe5 (X = Zr, Hf) has a large bandgap in its bulk form and a single layer of XTe5 is a QSH insulator candidate. However, the topological nature of the bulk material is still under debate because it is located close to the phase boundary of a strong topological insulator and a weak topological insulator (WTI). Here, using angle-resolved photoemission spectroscopy and scanning tunneling microscopy (STM)/scanning tunneling spectroscopy, we systematically studied the electronic structures of bulk HfTe5. Both the large bulk bandgaps and conductive edge states in the vicinity of the step edges in HfTe5 were observed, strongly suggesting a WTI phase in bulk HfTe5. Moreover, our STM experiment for the first time reveals the bulk band bending due to the broken symmetry near the step edge, making it an ideal platform for studying the development of edge states in the WTI and QSH insulator.
CRIS-Team Scopus Importer:2022-04-14